A method of quantifying torso shape to assess its influence on resistive drag in swimming - Papic, C.; McCabe, C.; Naemi, R.; Sanders, R. (ISBS Proceedings Archive (Michigan), 2019)
Torso shape characteristics such as cross-sectional area, curvatures and indentations influence the pressure distribution of fluid flow around the torso. The purpose of this study was to introduce a new method of quantifying torso shape using photographic imaging. The contours of the torso in the frontal and sagittal planes were obtained by tracing photographs of the swimmers. Anterior, posterior and lateral flow lines were interpolated to samples spaced at 1mm vertically and used to determine continuous form gradients of four elite male swimmers. The maximum rate of change in cross-sectional area was estimated from chest-waist and waist-hip by modelling each vertical sample of the torso as an ellipse. The method provides implications for discussion with coaches and athletes and future research to determine the role of torso shape in talent identification and swimming performance.